Promotion Role of Information Disclosure on Competitive Response of Sporadic Procurement in Universities - Ning, Yi-Zi (Advances in Social Sciences Research Journal, 2023)
The procurement amount of sporadic projects in universities is small. The procurement frequency is high. The time cannot be predicted. The target of the project is relatively simple, and the profit is low. Through network channel publicity information, we analyze potential suppliers and judge supply quality. Although large suppliers react passively and participate less, information dissemination through the network can improve the attention of small and medium-sized suppliers. Publishing information on the Internet is conducive to strengthening internal management and system construction. Announcements are issued to promote the supervision of the procurement process and promote competitive response. However, unpredictable non-competitive procurement projects will still exist.